Hydrogeochemical Characteristics and Genesis of the Chazi Geothermal Field Area in Tibet. (23rd September 2022) - Song, Mingzhong; Lang, Xujuan; Zhong, Zhennan; Kang, Fengxin; Nan, Dawa; Li, Haoting; Yu, Haowen; Liu, Shaoyun; Han, Sihang; Liu, Zhao
Abstract : The Chazi geothermal field area is located in the large region of Shigatse in southern Tibet. The geothermal resources in this area are abundant, but their exploitation and utilization are low. By studying the water chemistry and isotope characteristics of geochemical fluids in the study area, information on water chemistry, heat storage temperature, recharge source, recharge elevation, and circulation depth was obtained. These results provide a scientific theoretical basis for improving the genetic mechanism of high-temperature geothermal systems in the study area. The type of geothermal fluid hydrochemicals in this area is mainly HCO3 –Na. The isotopic geochemical method was used to determine that the recharge source of geothermal fluids was atmospheric precipitation, and the recharge elevation was 5200–6000 m. The geochemical thermometer, Na–K–Mg equilibrium diagram, and silica-enthalpy mixed model indicated the shallow and deep thermal storage temperatures of approximately 150 and 200°C, respectively, and the average circulation depth of 1163.38 m in the study area. Combined with the fracture structure and magmatic activity characteristics of the southwest Qinghai-Tibet Plateau, the source, storage, cover, and general situation of the area were preliminarily summarised, and the conceptual model of geothermal origin was established. The results can provide a scientific theoretical basis for the mechanism of high-temperature geothermal systems and subsequent drilling and resource development.